2013
DOI: 10.1126/science.1235451
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Observations as Voyager 1 Entered the Heliosheath Depletion Region

Abstract: Magnetic fields measured by Voyager 1 (V1) show that the spacecraft crossed the boundary of an unexpected region five times between days 210 and ~238 in 2012. The magnetic field strength B increased across this boundary from ≈0.2 to ≈0.4 nanotesla, and B remained near 0.4 nanotesla until at least day 270, 2012. The strong magnetic fields were associated with unusually low counting rates of >0.5 mega-electron volt per nuclear particle. The direction of B did not change significantly across any of the five bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
137
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(157 citation statements)
references
References 21 publications
18
137
2
Order By: Relevance
“…Also shown in Figure 4 are the vector direction of the magnetic field B V1, HDR in the heliosheath depletion region (HDR) measured at Voyager 1 (Burlaga et al 2013) and its antipode. As Voyager 1 continues along its trajectory toward the ISM, we expect that the magnetic field will rotate from its present direction to align with the unperturbed ISMF direction.…”
Section: Geometrical Model Of the Ribbon Peakmentioning
confidence: 99%
See 2 more Smart Citations
“…Also shown in Figure 4 are the vector direction of the magnetic field B V1, HDR in the heliosheath depletion region (HDR) measured at Voyager 1 (Burlaga et al 2013) and its antipode. As Voyager 1 continues along its trajectory toward the ISM, we expect that the magnetic field will rotate from its present direction to align with the unperturbed ISMF direction.…”
Section: Geometrical Model Of the Ribbon Peakmentioning
confidence: 99%
“…Although the ISMF polarity is not currently known, its estimated vector direction in the vicinity of the ribbon center ) suggests rotation of B V1, HDR (rather than its antipode) toward the ribbon center. The vector direction of the ideal Parker spiral magnetic field at the location of V1 (Burlaga et al 2013) is also shown for reference.…”
Section: Geometrical Model Of the Ribbon Peakmentioning
confidence: 99%
See 1 more Smart Citation
“…There are usually an infinite number of eigenfunctions, but the one with zero radial nodes is always the most unstable, if it is unstable at all. Across the transition the plasma pressure decreases and the magnetic field increases, so that the plasma beta drops from 5.5 in the inner heliosheath to 0.36 in the LISM, based on Voyager observations and models [3,12]. This configuration may become unstable and develop interchange perturbations because the curvature of magnetic field lines is directed into the region of high beta (sunward).…”
Section: Pos(icrc2015)214mentioning
confidence: 99%
“…At this time, it is generally agreed that the Voyager 1 space probe has crossed this boundary near 20012.65, and has been traveling through local interstellar medium (LISM) since then [1,2,3,4]. The key observations in favor of the crossing were (a) a rapid depletion of heliospheric ions, evidently as a result of their escape into interstellar space, (b) an increase in galactic cosmic rays followed by virtually constant intensity for the next two years, (c) a change in the direction and strength of the magnetic field by about 20 • relative to the primarily azimuthal field in the heliosphere, (d) detection of plasma waves at frequencies indicating a plasma density of the order of 0.08 cm −3 , some 30 times the density in the inner heliosheath (the region between the heliopause and the termination shock), and (e) a near absence of magnetic fluctuation characteristic of the interstellar medium [5].…”
Section: Introductionmentioning
confidence: 99%